Modulation of Peripheral Immune Cell Subpopulations After RapidArc/Moderate Hypofractionated Radiotherapy for Localized Prostate Cancer: Findings and Comparison With 3D Conformal/Conventional Fractionation Treatment - Fiorella D’Auria; Teodora Statuto; Luciana Rago; Antonietta Montagna; Giovanni Castaldo; Irene Schirò; Anna Zeccola; Teresa Virgilio; Gabriella Bianchino; Antonio Traficante; Alessandro Sgambato; Vincenzo Fusco; et al. (Frontiers in Oncology, 2022)
Radiotherapy (RT) is an important therapeutic option in patients with localized prostate cancer (PC). Unfortunately, radiation treatment causes a decrease in peripheral lymphocytes and, consequently, influences the patients’ immune status. Our aim was to study changes in peripheral blood immune cell subpopulations after RT and during 6 months’ follow-up in 2 groups of PC patients irradiated with different techniques and dose fractions with curative intent. We also investigated the presence of correlation between immune cell modulation and genitourinary or gastrointestinal toxicity. We enrolled 44 patients treated with curative RT (RapidArc/hypofractionation regimen or 3D conformal/conventional fractionation) for localized PC. Total white blood cell (WBC), absolute lymphocyte counts (ALCs), and peripheral immune cell subpopulations were analyzed at baseline, at the end of RT, and 3 and 6 months after the end of RT. WBC and ALC greatly decreased at the end of RT with a trend to recover at 6 months’ follow-up in the hypofractionation group but not in the conventional one. Furthermore, B, total T, T CD4+, T CD8+, and NK cell values dropped significantly in both groups at the end of RT, with a minor decrease detectable in the hypofractionation group for B, total T, and T CD4+ lymphocytes with respect to the other technique/fractionation group. Double-negative T (DNT), double-positive T (DPT), and NKT cells significantly decreased at the end of RT with a slight tendency to recover values during follow-up, particularly in the hypofractionation group. No correlation with genitourinary or gastrointestinal toxicity was found. In this study, we showed, for the first time, the effects of RapidArc/moderate hypofractionation RT on immune cell subsets in patients treated for localized PC. Due to the growing interest in minority T-cell subpopulations for immunotherapy, we also reported longitudinal monitoring of the effects of RT on DNT, DPT, and NKT, which was never studied before. Our preliminary data highlight the importance of considering the effects of different RT techniques/fractionation regimens on peripheral immune cells, in the era of RT and immunotherapy combination.